Efficacy of Cell Wall‐Deficient Spheroplasts Against Experimental Murine Listeriosis. (July 2015) - Ansari, M. A.; Zia, Q.; Kazmi, S.; Ahmad, E.; Azhar, A.; Johnson, K. E.; Zubair, S.; Owais, M.
Abstract Various strategies adapted to develop an efficient vaccine against foodborne pathogen, Listeria monocytogenes, have met with little success. Spheroplasts (bacterial cell devoid of cell wall) are likely to undergo membrane–membrane fusion, leading to the delivery of their content to the cytosol of antigen‐presenting cells, thus facilitating MHC class I antigen processing and presentation. In this study, we evaluated the prophylactic potential of Listeria spheroplast‐based vaccine against experimental murine listeriosis in comparison with heat‐killed Listeria (HKL) and archaeosome‐entrapped Listeria whole‐cell protein (LWCP). Compared with HKL, the spheroplast‐based vaccine was found to evoke better Th1 response as exhibited by the presence of type 1 cytokines in the host (interferon‐γ and IL‐12) and a high IgG2a/IgG1 ratio. Robust lympho‐proliferative efficacy was apparent in both spheroplast‐immunized and archaeosome‐entrapped LWCP‐immunized groups. The upregulation of costimulatory and effector memory markers upon immunization with spheroplasts was found to be at par with that evoked by archaeosome‐entrapped LWCP‐immunized group. Central memory response in gated CD8+ T cell was much higher in spheroplast‐immunized animals when compared with archaeosome‐entrapped LWCP group. The data presented here clearly demonstrate that spheroplasts evoked a robust immune response and offer better prophylactic potential against L. monocytogenes.